Identifikasi Fosil Kayu asal Bogor dan Lebak (Identification of Wood Fossil from Bogor and Lebak) - Andianto Andianto; Agus Ismanto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
Fossil wood is a heritage of flora history from a certain area. Species determination and age estimation are conducted on two sample of fossil wood which are collected from Bogor and Lebak districts. Anatomical features on transversal, radial and tangential sections were identified using microscope of Imager-A1m type. Anatomy description refers to the International Association of Wood Anatomists (IAWA) list of microscopic features for hardwood identification. The age estimation of the fossil wood was determined based on geological map analysis. The identified anatomical features of the first sample is vessels which mostly solitaire, radial and diagonal multiples; diffuse, vasicentric, confluent and narrow bands or lines up to three cells wide parenchyma; axial resin canals are arrayed in long tangential lines. These anatomical characteristics are belonging to Shoreoxylon sp. (meranti). The identified anatomical characteristics of the second sample is exclusively solitary vessels; diffuse and vasicentric parenchyma; and possesses tangential resin canals with diameter smaller than vessel diameter. These anatomical characteristics are owned by Dryobalanoxylon sp. (kamper). The age estimation of the wood fossils are 2.5 to 0.01 million years old (early to middle Pleistocene period).Keywords: Bogor, Dryobalanoxylon, fossil wood, Lebak, Shoreoxylon